INTERRELATION OF SCIENCE AND EDUCATION IN ENGINEERING HIGHER EDUCATIONAL INSTITUTIONS: CHALLENGES AND OPPORTUNITIES (American Journal of Technology and Applied Sciences, 2023)
The article under discussion depicts the problems of the relationship between science and engineering higher educational institutions and possible approaches to overcoming them with the application of new technologies, creation of more flexible study programmes and active participation of students in research activities. The authors of the article consider that the case study method in engineering higher educational institutions offers a wide range of educational opportunities. It is necessary to use such educational methods through which students will be able to acquire both knowledge and skills and form the necessary set of professional competences. Thanks to the effective organisation of the educational process the student will be competitive in the labour market and will attract the attention of employers of serious and promising companies.